The production process of "Book of Reminiscence", a 3rd person historical role-playing game - Kong, Lingxiao (Nanyang Technological University, 2023)
This report presents an exhaustive account of the production process for a historically-themed role-playing game "Book of Reminiscence" in the Song Dynasty. The game revolves around the journey of a scholar named Song Shu, who unexpectedly becomes the owner of his family's longstanding bookstore following the untimely demise of his parents. Additionally, the narrative incorporates a mystical engraved stone as a critical element. The game is designed as a third-person perspective PC game developed using Unreal Engine 5. It features a unique hybrid approach, combining 2D pixel-style characters with a 3D voxel-style environment. Players will engage in puzzle-solving activities within the intricately designed two-story bookstore setting.